2000
DOI: 10.1007/s002680010170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemia/Reperfusion as a Systemic Phenomenon on Anastomotic Healing in the Left Colon

Abstract: Intestinal ischemia/reperfusion provokes a local inflammatory response leading to a systemic inflammatory state. In this study we aimed to assess the effects of intestinal ischemia/reperfusion injury on anastomotic healing in the left colon with an intact vascular supply. A total of 94 Wistar albino rats were divided into three groups: sham-operated control (group I, n = 25), 30 minutes of intestinal ischemia/reperfusion (group II, n = 40), and 7-day allopurinol pretreatment and intestinal ischemia/reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 28 publications
4
38
0
1
Order By: Relevance
“…Preoperative or intraoperative IRIs may also affect wound healing and decrease anastomotic durability. [3] Most of the general factors suggest that the vasoconstrictive effects are the cause of local ischemia and dehiscence of an anastomosis. Perfusion and the state of local oxygenation are some of the most important factors for healing gastrointestinal anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preoperative or intraoperative IRIs may also affect wound healing and decrease anastomotic durability. [3] Most of the general factors suggest that the vasoconstrictive effects are the cause of local ischemia and dehiscence of an anastomosis. Perfusion and the state of local oxygenation are some of the most important factors for healing gastrointestinal anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that segmental small intestinal, unilateral lower extremity, and unilateral renal IR significantly delay anastomotic healing in the right colon. Similarly, Kuzu et al [3] showed that reperfusion stress after SMA ischemia cause a delay in the anastomotic healing process in the left colon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other studies have suggested that burst occurring outside of the anastomosis line is frequent during BP measurements performed after postoperative day 5. [47][48][49][50][51] In the present study, BP was measured on the postoperative day 5. It was observed that burst occurred outside of the anastomosis line in 4 rats.…”
Section: Discussionmentioning
confidence: 99%